Les Archives de France et les archives d'entreprises - Brot, Isabelle (Gazette des archives, 1979)

Les archives d'entreprises en Suède : bientôt une solution d'ensemble ? - Clemensson, Per (Gazette des archives, 1979)
Business archives in Sweden ; soon a general solution ? Among private archives in Sweden, business archives are the most important and threatened part. The law gives them little protection. Some firms have organised central repositories for the archives of all their branches. Other solutions have been found by a co-operation between private firms and local administrations, or by the aid of State money. In 1978 the Swedish Employers' Association launched an enquiry, which is hoped to lead to a general solution of the problem.

Les archives d'entreprises dans les départements - Chomel, Vital (Gazette des archives, 1974)

Les archives d'entreprises aux Archives nationales - Brot, Isabelle (Gazette des archives, 1974)

Des archives à sauver : les archives contemporaines du mouvement ouvrier - Cavignac, Jean (Gazette des archives, 1977)